Os bnei anussim brasileiros: religião, etnicidade e reivindicações identitárias - Santos, Nelson Santana (2024)
This thesis deals with a social phenomenon that clearly exposes the often problematic relationship between ethnicity and religiosity as constitutive dimensions of contemporary identity processes. Its focus of analysis is on aspects relating to the identity representations of a group whose claims to belonging circulate around a religious and cultural segment in which religious identity is directly linked to the ethnic factor. These are the bnei anussim: a group of people who, because of their selfidentification as descendants of Jews forcibly converted to Christianity, claim Jewish identity for themselves and share the desire to be part of this identity and religious context. Throughout the 20th and even the 21st centuries, various individuals and groups began to claim bnei anussim or marrano ancestry and identity (both in Brazil and in other parts of America, such as Mexico and the United States). It's worth saying that a considerable proportion of these individuals, considering themselves to be descendants of Jews whose religiosity was coercively altered, want to be recognised as legitimate members of the Jewish community, religion and, consequently, identity. However, according to the legal precepts of Judaism (contained in the Halakah) the main criteria for considering someone a Jew are birth to a Jewish mother or conversion through a specific ritual for this purpose. The problematic aspect of the issue stems, therefore, from the fact that Judaism (at least in its more traditional forms) is a social grouping that self-identifies as both a religion and an ethnicity. In this sense, original and integral belonging to the Jewish group requires a double qualification: you have to practise the Jewish religion and you have to have been born to a Jewish mother. Even though the bnei anussim make an effort to assimilate Jewish religious practices, in most cases they can hardly fulfil the second requirement. The only gateway to Judaism is conversion (giyur, in Hebrew) - which in turn is seen by many of its members as a disrespect to the memory of their ancestors who fought to maintain their Jewish traditions, albeit in secret. Instead of "conversion" (giyur), some bnei anussim want to be admitted through the process of "return" (teshuvah, in Hebrew), which is not normally accepted by the institutional leadership of Judaism. From a sociological point of view, it is obviously not necessary to assess the plausibility of the arguments put forward by the parties involved in this dispute. However, it deserves special attention to glimpse and understand sociologically the strategies adopted by both groups, both in face-to-face interactions and in symbolic, discursive and cultural representations, and the social repercussions of these strategies. In this sense, this qualitative research, based on recent approaches to identity processes, especially those influenced by cultural studies, proposed an analysis of the discursive strategies mobilised by the bnei anussim with a view to circumventing the obstacles faced in their relations with established Judaism. The main objective of the research, which we believe was successfully achieved, was to prove that the way in which the bnei anussim have adopted claiming strategies with the aim of mitigating the identity legitimacy credentials of an identity ideally seen as global (the Jewish identity), through the displacement of these credentials from the religious and biological sphere to the local historical and mnemonic sphere (by reinforcing the significance of the specificities resulting from the secular prohibition of Jewish practices to which their Brazilian and Portuguese ancestors were subjected) configures a set of typically contemporary and glocal strategies. In this way, we propose that the study of the glocal performance of the bnei anussim makes an important contribution to the debates on identity processes 10 and their specific configurations in the current stage of globalised and mediatised society.